Challenges Faced by CIOs in cloud and IoT based organizations- A Study on IT and Business Leaders - Jipson George; Mohammed Nazeh (JOIV : International Journal on Informatics Visualization, 2019)
The Internet of Things (IoT) is turning into the following Internet-related insurgency. It enables billions of gadgets to be associated and speak with one another to share data that enhances the nature of our day by day lives. Then again, Cloud Computing gives on-request, advantageous and adaptable system which makes it conceivable to share computing assets; surely, this empowers dynamic information integration from different information sources. There are numerous issues hindering the effective implementation of both Cloud and IoT affecting the role of a chief information officer (CIO).The integration of Cloud Computing with the IoT is the best path on which to conquer these issues. The immense number of assets accessible on the Cloud can be to a great degree advantageous for the IoT, while the Cloud can acquire exposure to enhance its confinements with true protests in a more powerful and conveyed way. This paper gives an outline of the integration of the Cloud into the IoT by featuring the integration advantages and implementation challenges. Cloud computing has developed enormously throughout the years. Since the term appeared in mid 90s it was produced and being worked upon to make it a conceivable answer for business information stockpiling and availability issues. Expansive undertakings are progressively discovering cloud an affable arrangement even inside their stringent hierarchical approaches.Cloud has been such advanced that there is a surge of executing virtualization among CIOs. This has prompt a larger number of complexities than arrangements. The issues with cloud implementation are for the most part because of the scurry without legitimate investigation of one's circumstances and necessities previously. Following is a concise dialog on the difficulties looked by organizations amid executing cloud computing.This study focuses on the challenges faced by CIOs in a cloud and IOT based organization. This study will analyze the major challenges in cloud and IOT environments like security, privacy, performance, compliance, governance, portability, interoperability, lack of resources, cost management etc. As part of this study a survey was conducted on 400 plus IT and business leaders from various organizations from almost 30 plus countries and their responses are recorded and analyzed as part of this study